Nitrous oxide and methane emissions from beef cattle excreta deposited on feedlot pen surface in tropical conditions. (February 2021) - Maciel, Isabella C.F.; Barbosa, Fabiano A.; Alves, Bruno J.R.; Alvarenga, Ramon C.; Tomich, Thierry R.; Campanha, Mônica M.; Rowntree, Jason E.; Alves, Filipe C.; Lana, Ângela M.Q.
Abstract: As feedlot beef production systems are expanding into tropical climates, considerably less is known on their environmental impact specific to these regions. Our objective was to investigate the dynamics of nitrous oxide (N2 O) and methane (CH4 ) fluxes in a feedlot system representative of Brazil, in order to aggregate new emission data for the characterization of intensive cattle raising in tropical regions. Excreta was obtained from Nellore steers in a feedlot ( n  = 25, BW = 393 ± 31 kg). Urine (1.3 L) and feces (1.3 kg) were applied separately in plots on an open-lot feedlot pen surface at the beginning of the trial and fluxes were monitored 92 d with static chambers. Although CH4 fluxes were variable, all treatments were a sink for CH4 as the average of the monitoring period (−8.9, −3.1, and −15.4 μg C m −2  h −1 for feces, urine, and control, respectively). The N2 O fluxes were higher in the urine affected area, which was related to the higher soil moisture and mineral N availability in comparison to the area with feces. The occurrence of rainfall from 67 to 70 DAA was determinant of very high N2 O fluxes either for urine or feces. Hence, GHG emissions from individual excreta were characterized by a period of small but significant fluxes, followed by a period of indistinguishable fluxes at the background level. A third period after rainfall portrayed the large impact of excreta on GHG emissions from the feedlot. The direct N2 O emission factor (EF) for the N in urine was significantly higher than for the N in feces (2.83 vs. 0.32%, respectively, P  < 0.0001), and combining both resulted in an EF for the N in excreta of 1.83%, which is 8.5% less than IPCC default EF for dry lot systems. From the calculated direct emissions of N2 O, gas monitoring of urine and feces in separate should be also considered for the development of emission factors for inventory purposes in tropical environments. For the regions where feedlots are used in the dry season for finishing cattle, cleaning pens regularly can contribute substantially to mitigate N2 O emissions as suggested by the results of the present study. Graphical abstract: Unlabelled Image Highlights: N2 O emission was greater from urine than from feces. The period after rainfall portrayed the large impact of excreta on GHG emissions from the feedlot. CH4 emission seems to be of lower importance when dry conditions prevail. Urine treatment had higher soil ammonium and nitrate concentrations than feces. N2 O emission factor from urine was significantly higher than the feces.